Android to gynoid fat ratio and its association with functional capacity in male patients with heart failure - Marcelo Rodrigues Dos Santos; Guilherme Wesley Peixoto daFonseca; Letícia Pironato Sherveninas; Francis Ribeiro deSouza; Antônio Carlos Battaglia Filho; Caio Eduardo Novaes; Rosa Maria Rodrigues Pereira; Carlos Eduardo Negrão; Antônio Carlos Pereira Barretto; Maria‐Janieire de Nazaré Nunes Alves (ESC Heart Failure)
Abstract Aims We studied the association between android (A) to gynoid (G) fat ratio and functional capacity (peak VO2) in male patients with heart failure with reduced ejection fraction (HFrEF). Methods and results We enrolled 118 male patients with HFrEF with left ventricular ejection fraction (LVEF) <40%. Body composition (by using dual x‐ray absorptiometry) and peak VO2 (by cardiopulmonary exercise testing) were measured. Sarcopenic obesity was defined according to the Foundation for the National Institutes of Health criteria (FNIH). Blood sample for metabolic and hormonal parameters were measured. Fifteen patients (12.7%) showed sarcopenic obesity (body mass index > 25 kg/m2 with FNIH index < 0.789). The median A/G ratio was 0.55. A/G ratio > 0.55 was detected in 60 patients. Relative peak VO2 was lower in patients with A/G ratio > 0.55 than in patients with A/G ratio <0.55 (18.7 ± 5.3 vs. 22.5 ± 6.1 mL/kg/min, P < 0.001). Logistic regression analysis showed A/G ratio >0.55 to be independently associated with reduced peak VO2 adjusted for age, body mass index, LVEF, presence of sarcopenia, anabolic hormones, and haemoglobin (odds ratio 3.895, 95% confidence interval 1.030–14.730, P = 0.045). Conclusions Body fat distribution, particularly android and gynoid fat composition, together with other cofactors, might have an important adverse role on functional capacity in male patients with HFrEF. Future studies are needed to address possible mechanisms involved in this relationship.